Analisis Risiko dan Potensi Cryptocurrency sebagai Instrumen Investasi Digital di Indonesia - Mohammad Adit Setiawan; nurul lathifah (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study analyzes the risk and potential of cryptocurrency as a digital investment instrument in Indonesia using daily data of Bitcoin (BTC), Ethereum (ETH), gold, and the Jakarta Composite Index (IHSG) from 2020 to 2024. A descriptive-quantitative approach was applied, combining literature review and secondary data analysis. Logarithmic returns, GARCH(1,1) volatility models, and Value at Risk (VaR) with Conditional VaR (CVaR) at 95% and 99% confidence levels were employed. The results show that BTC and ETH generated extraordinary annual returns above 170% in 2020 and over 110% in 2023, but also recorded negative returns in crisis years such as 2022 and 2024. GARCH estimations confirm volatility clustering, with Ethereum showing stronger persistence than Bitcoin. VaR analysis indicates potential daily losses up to −13.2% for ETH and −10.3% for BTC at the 1% worst case, compared to only −2% for gold and IHSG. Scatter risk–return plots place cryptocurrencies in the high risk–high return quadrant, while gold and IHSG remain low risk–low return. Literature findings highlight regulatory gaps, speculative behavior, and low financial literacy among Indonesian millennial and Gen Z investors. Overall, cryptocurrency may serve as an alternative for risk-tolerant investors, contingent upon stronger regulation, education, and risk management.